2008
DOI: 10.1177/0310057x0803600611
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Base Effects of a Bicarbonate-Balanced Priming Fluid during Cardiopulmonary Bypass: Comparison with Plasma-Lyte 148. A Randomised Single-Blinded Study

Abstract: Fluid-induced metabolic acidosis can be harmful and can complicate cardiopulmonary bypass. In an attempt to prevent this disturbance, we designed a bicarbonate-based crystalloid circuit prime balanced on physico-chemical principles with a strong ion difference of 24 mEq/l and compared its acid-base effects with those of Plasma-Lyte 148, a multiple electrolyte replacement solution containing acetate plus gluconate totalling 50 mEq/l. Twenty patients with normal acid-base status undergoing elective cardiac surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 52 publications
3
22
0
Order By: Relevance
“…We estimated that we would need 10 patients in each group, a total sample size of 20 patients, to have a power of 0.8 to detect a 2 mmol/l difference in base-excess between the two solutions. This is in line with the detection of a base-excess difference in other studies [7][8][9] . All patients underwent elective primary coronary revascularisation.…”
Section: Methodssupporting
confidence: 93%
“…We estimated that we would need 10 patients in each group, a total sample size of 20 patients, to have a power of 0.8 to detect a 2 mmol/l difference in base-excess between the two solutions. This is in line with the detection of a base-excess difference in other studies [7][8][9] . All patients underwent elective primary coronary revascularisation.…”
Section: Methodssupporting
confidence: 93%
“…Gluconate may protect against post ischemic cardiac dysfunction and oxidative injury[73], however there is lack of data on acetate and gluconate levels after PL 148 administration in most surgical settings. In a phase II clinical trial of PL 148 vs a bicarbonate-based cardiopulmonary bypass prime solution, there was a significant increase in unmeasured anions levels after PL 148 administration, which was still present, albeit in smaller concentrations prior to cessation of CPB[74]. Liskaser et al[19] reported similar findings.…”
Section: Discussionmentioning
confidence: 88%
“…Gluconate has also been incorporated into some enteral and parenteral pharmaceutical preparations. The principal benefit of bicarbonate-balanced fluids demonstrated thus far, apart from avoidance of exogenous anions, is the ability to achieve a well balanced acid-base status across CPB [8]. Also, there is now evidence that added sodium bicarbonate may exert a renal protective effect in CPB [29].…”
Section: Discussionmentioning
confidence: 99%
“…A potential complication [2] of CPB is metabolic acidosis, which is influenced by the CPB circuit priming fluid [3,4]. Attempts to prevent metabolic acidosis have entailed alterations to circuit prime fluids, including partial replacement of chloride by rapidly metabolised anions such as L-lactate [5,6], acetate and gluconate [3,7], or else by bicarbonate [8]. Plasma-Lyte 148 (Baxter, Toongabbie, NSW, Australia) is a crystalloid CPB prime fluid in common use in Australia and New Zealand (personal communication, Andrew McLaren, Baxter, Australia) in about 7% of surveyed units in the UK [9] and in some units in North America [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation